2020
DOI: 10.1108/rjta-02-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

A DEMATEL-MABAC-based approach for grading and evaluation of jute fibers

Abstract: Purpose Due to several unique characteristics, such as high tensile strength, low extensibility, high frictional resistance, biodegradability, eco-friendliness and cheapness, Jute ranks second just after cotton with respect to its worldwide consumption and production. To overcome the difficulties of the existing Jute grading procedure, this paper aims to focus on the application of decision-making trial and evaluation laboratory (DEMATEL) and multi-attributive border approximation area comparison (MABAC) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It is probed that the decision making based on customized designs, reliable tools, vigorous techniques, strategic provisions are crucial and their integration may lead in assuming reliable results (Yazdani et al, 2017;Luthra and Mangla, 2018;Sharma et al, 2021a). Accordingly, the present study has gripped the boundaries of AHP (Awasthi et al, 2018;Celik and Akyuz, 2018), DEMATEL (Agarwal et al, 2020;Sen et al, 2021), ANP (Abdel-Baset et al, 2019;Nimawat and Gidwani, 2021), Extended MOORA (Arabsheybani et al, 2018;Zolfaghari and Mousavi, 2021) and SAW (Piasecki et al, 2019;Sahu et al, 2019) techniques to define the integral form of these universally valued decision-making techniques treasured by the quality researchers. It is found that DEMATEL can define the cause and effect relationship amongst elementary metrics with ease computation rather than obliging hierarchical or network relationship and accordingly DEMATEL is used in this study to ease disclose the causal relationships among LARG metrics and to assist in understanding the crucial ones.…”
Section: Rationalization About Using Integrated Techniques In Dsfmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probed that the decision making based on customized designs, reliable tools, vigorous techniques, strategic provisions are crucial and their integration may lead in assuming reliable results (Yazdani et al, 2017;Luthra and Mangla, 2018;Sharma et al, 2021a). Accordingly, the present study has gripped the boundaries of AHP (Awasthi et al, 2018;Celik and Akyuz, 2018), DEMATEL (Agarwal et al, 2020;Sen et al, 2021), ANP (Abdel-Baset et al, 2019;Nimawat and Gidwani, 2021), Extended MOORA (Arabsheybani et al, 2018;Zolfaghari and Mousavi, 2021) and SAW (Piasecki et al, 2019;Sahu et al, 2019) techniques to define the integral form of these universally valued decision-making techniques treasured by the quality researchers. It is found that DEMATEL can define the cause and effect relationship amongst elementary metrics with ease computation rather than obliging hierarchical or network relationship and accordingly DEMATEL is used in this study to ease disclose the causal relationships among LARG metrics and to assist in understanding the crucial ones.…”
Section: Rationalization About Using Integrated Techniques In Dsfmentioning
confidence: 99%
“…A.2. Deployment of DEMATEL "Decision-Making Trial and Evaluation Laboratory technique" directly computes the interaction relationship among variables (G€ olc€ uk and Baykaso glu, 2016; Agarwal et al, 2020). It converts complex system into cause and effective relationship (Sen et al, 2021).…”
Section: Gmmentioning
confidence: 99%
“…Case study Methodology Objective (Chatterjee et al, 2017) India MABAC Machining process selection (Zhu et al, 2018) China IVPFS-Entropy-MABAC Evaluation and assessment of potential product failure risks (Nunić, 2018) -FUCOM-MABAC Assessment of PVC manufacturing centres (Can and Toktas, 2018) Turkey TFS-DEMATEL-MABAC Assessment of potential warehouse risks (Chakraborty et al, 2020b) -R-Entropy-MABAC Machining process selection (Agarwal et al, 2020) India DEMATEL-MABAC Evaluation of jute fibers for manufacturing purposes (Bose et al, 2020) India ARAS-MABAC Material selection (Bose et al, 2020) India BWM-MABAC Optimizing the wear parameter of CrN/TiAlSiN coating strategic importance sectors such as national infrastructure and defence (Haraguchi et al, 2017). Manufacturing systems include the manufacturing and processing of items and result in either creation of new goods or in value addition.…”
Section: Referencesmentioning
confidence: 99%
“…Usually, employees are treated equally but in a culturally appropriate manner (Sonja, 2001). Poor HRM is one of the most significant universal delay factors in international project execution (Zidane and Andersen, 2018). Globalization demands HR professionals to take a proactive role in the project's success.…”
Section: Human Resource Management In International Projectsmentioning
confidence: 99%
“…Employee strikes may halt the functioning of several functional departments of the project. International PRM is a continuous process and these disputes and strikes can reduce its effectiveness (Wenche et al, 2013;Zidane and Andersen, 2018).…”
Section: Human Resource Barriers To Risk Management In International Projectsmentioning
confidence: 99%